The Relevance and Impact of Academic Supervision on Educational Excellence in Secondary Schools - Sembiring, Desy Anita Karolina; Tijow, Meylani Aljeinie (Graduate Program Magister Manajemen Pendidikan, 2025)
This study examines the practice of academic supervision, its effectiveness in enhancing learning quality, and its impact on educational excellence in secondary schools in Kota Jayapura. Using a mixed-method approach with a sequential explanatory strategy, the research collected data from 138 respondents through surveys and in-depth interviews. Results show that academic supervision practices vary between schools, with systematic and collaborative approaches yielding better outcomes. The overall effectiveness is high (28.32 out of 30), positively impacting teachers’ and students’ learning quality, student achievement, and psychological-emotional well-being, though implementation challenges persist. The research introduces an integrated framework combining adaptive and collaborative supervision approaches tailored to Kota Jayapura’s local context. This study enhances understanding of supervision implementation in regions with significant socio-cultural diversity and provides recommendations for improving supervision effectiveness in diverse educational settings.